PPR (polypropylene random copolymer) pipe with low-temperature-resistant toughness and preparation process of PPR pipe
By preparing boronene microspheres and composite materials, combined with blended injection molding and graded pressurized annealing processes, the brittleness problem of PPR pipes under low temperature conditions is solved, and its low temperature toughness and mechanical properties are significantly improved.
Patent Information
- Application Number
- CN202510139317.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
PPR pipes are highly brittle under low temperature conditions, resulting in poor performance during storage, transportation, installation and use, limiting their application range.
The composite of boronene microspheres, polystyrene, boronene microspheres and calcium pimethenate was prepared, combined with blended injection molding and graded pressurized annealing technology to improve the crystallinity and mechanical properties of PPR pipes.
It significantly improves the low-temperature toughness and mechanical properties of PPR pipes, shortens the annealing and insulation time, improves production efficiency, and reduces the internal stress of the material.
Smart Images

Figure CN119842160A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer toughening and modification, in particular to a PPR pipe with low-temperature resistance and toughness and a preparation process thereof. Background Art
[0002] Random copolymer polypropylene (PPR) has been widely used due to its excellent comprehensive properties (good flexibility, corrosion resistance, high temperature and high pressure resistance, waterproof and scale resistance, long service life, etc.). However, during the synthesis process of PPR, the ethylene monomer is randomly distributed in the long propylene chain, and the ethylene monomer is controlled between 3% and 5%. The ethylene content and the polymerization mode of ethylene and propylene lead to the low-temperature brittleness of PPR pipes. In addition, during the cooling and shaping process of PPR pipes, the molecular chain will form a reversible high-elastic deformation. This high-elastic deformation is frozen and stored in the PPR pipe in the form of potential energy. When the material is subjected to impact, the pipe is also prone to stress cracking. The low-temperature brittleness of PPR pipes greatly affects its storage, transportation, installation and use, and limits its scope of application.
[0003] In addition to using blended elastomers, adding β-nucleating agents, and blending inorganic rigid nanoparticles to improve the low-temperature impact resistance of PPR, the industry prefers to use annealing treatment, a green and environmentally friendly method, to remove the internal stress of PPR pipes, increase their crystallinity, and thus improve their low-temperature toughness. However, traditional annealing treatments usually need to be maintained for a long time, reducing production efficiency. In addition, it is difficult to maintain consistent temperature and uniform heat distribution in actual operations, which may lead to uneven material properties. Ordinary annealing treatments often cannot effectively improve the crystallinity of the material, resulting in poor performance in mechanical properties and cold resistance. The temperature gradient during the cooling process may also regenerate internal stress, affecting the long-term performance of the pipe. Summary of the invention
[0004] In order to solve the above technical defects, the present invention has developed a preparation process of a PPR pipe with low-temperature resistance and toughness, which can improve the production efficiency and crystallinity of the PPR material and reduce the internal stress of the material. The prepared PPR pipe has good mechanical properties and low-temperature toughness.
[0005] A preparation process of a PPR pipe with low temperature toughness resistance comprises the following steps:
[0006] S1: Preparation of Borophene Microspheres
[0007] Boron powder, a ball milling solvent and a tungsten steel grinding ball are mixed and ball milled to obtain ball milled boron powder, the ball milled boron powder is ultrasonically dispersed in a sulfuric acid solution, and after standing, the powder is filtered, washed and dried in sequence to obtain pretreated boron powder, polyvinyl pyrrolidone is dissolved in deionized water to obtain a polyvinyl pyrrolidone solution, and the pretreated boron powder is ultrasonically dispersed in the polyvinyl pyrrolidone solution, and boronene microspheres are obtained after atomization and drying;
[0008] S2: Composite of polystyrene, boron nitride microspheres and calcium pimelate
[0009] Potassium persulfate, polyvinyl pyrrolidone and deionized water are mixed and stirred while nitrogen is introduced, acrylic acid and styrene are added and stirred, the temperature is increased in a nitrogen atmosphere for pre-reaction, boron nitrate microspheres are added, the temperature is continued to be increased after stirring for reaction, and polystyrene-borene microspheres are obtained by drying, the polystyrene-borene microspheres are ultrasonically dispersed in anhydrous ethanol, calcium nitrate is added, the temperature is increased and stirred, after standing, a pimelic acid ethanol solution is added and stirred evenly, the reaction is kept warm, and then filtered and dried to obtain calcium pimelic acid / polystyrene-borene microspheres;
[0010] S3: Compound injection molding and graded pressure annealing of PPR pipes
[0011] Calcium pimelate / polystyrene-borophene microspheres and random copolymer polypropylene are mixed and placed in a twin-screw extruder for co-extrusion and pelletization to obtain a blended masterbatch. The blended masterbatch is injection-molded by an injection molding machine and then cooled and solidified to obtain an injection-molded PPR pipe. The injection-molded PPR pipe is placed in a high-pressure and high-temperature annealing furnace for three-stage pressurized and heated annealing treatment to obtain a PPR pipe with low-temperature resistance and toughness.
[0012] Furthermore, step S1 of preparing borophene microspheres comprises the following steps:
[0013] S1.1: 2-3 parts by weight of boron powder, 4-6 parts by weight of ball milling solvent and 30-35 parts by weight of tungsten steel grinding balls with a particle size of 1-2 mm are placed in a ball mill, and then placed in a high-energy ball mill, the rotation speed is adjusted to 400-600rpm, and ball milling is performed for 6-8 hours to obtain ball-milled boron powder, and the ball-milled boron powder and a sulfuric acid solution with a mass percentage concentration of 20-25% are mixed in a solid-liquid ratio of 1: (8-10) and placed in a container, and ultrasonic dispersion is performed at a power of 400-450W for 25-30 minutes using an ultrasonic disperser, and then allowed to stand for 1-1.5 hours, filtered, rinsed with deionized water for 3-4 times, and then placed in an oven and dried at 65-70°C to obtain pretreated boron powder;
[0014] S1.2: Mix polyvinyl pyrrolidone and deionized water in a mass ratio of 1:(4-5) and stir until the polyvinyl pyrrolidone is completely dissolved to obtain a polyvinyl pyrrolidone solution, mix 2-3 parts by weight of pretreated boron powder and 4-6 parts by weight of polyvinyl pyrrolidone solution and place them in an ultrasonic disperser, perform ultrasonic dispersion at a power of 400-450 W for 15-20 minutes, then place them in a spray dryer, and perform atomization drying at a temperature of 120-150°C under a nitrogen atmosphere to obtain boron olefin microspheres.
[0015] Furthermore, step S2 of compounding polystyrene, borophene microspheres and calcium pimelate comprises the following steps:
[0016] S2.1: 1-2 parts by weight of an initiator and 0.3-0.4 parts by weight of polyvinyl pyrrolidone are placed in a container, 80-100 parts by weight of deionized water are added, and nitrogen is introduced into the resulting mixed solution while stirring at a stirring speed of 500-600 rpm for 30-40 minutes, then 1-1.5 parts by weight of acrylic acid and 4-4.5 parts by weight of styrene are added, and the mixture is stirred at a stirring speed of 300-350 rpm for 15-20 minutes, and then placed in a nitrogen atmosphere, heated to 45-50° C. for 3-4 hours of pre-reaction, and then 1.5-2 parts by weight of boron nitride microspheres are added, and the mixture is stirred at a stirring speed of 300-350 rpm for 20-25 minutes, and then the temperature is continued to be raised to 80-85° C. for 10-12 hours of reaction, and polystyrene-boron nitride microspheres are obtained after drying;
[0017] S2.2: 4-6 parts by weight of polystyrene-borophene microspheres and 60-80 parts by weight of anhydrous ethanol are mixed and placed in an ultrasonic disperser, and ultrasonic dispersion is performed at a power of 500-550 W for 20-25 minutes, and then 0.2-0.3 parts by weight of calcium nitrate are added, and the mixture is stirred at a stirring speed of 200-250 rpm at 60-65° C. for 30-35 minutes, and then allowed to stand for 30-35 minutes, and 12-16 parts by weight of ethanol solution of pimelic acid are added and stirred evenly, and the temperature is maintained at 60-65° C. for reaction for 2-3 hours to obtain a reaction dispersion liquid, and the reaction dispersion liquid is filtered to obtain a solid substance, which is then placed in an oven for drying at 70-75° C. to obtain calcium pimelic acid / polystyrene-borophene microspheres.
[0018] Furthermore, step S3 of the blending injection molding and graded pressurization annealing of the PPR pipe comprises the following steps:
[0019] S3.1: Calcium pimelate / polystyrene-borophene microspheres and random copolymer polypropylene are added into a mixer at a mass ratio of 1:(5-6) and mixed evenly to obtain a premix, the premix is placed in a twin-screw extruder, and melt-blended and extruded at a processing temperature of 200-225°C, a current intensity of 13-15mA, and a rotation speed of 100-150rpm, and pelletized by a pelletizer to obtain a blended masterbatch, and the blended masterbatch is injected into a closed mold by an injection molding machine, and then cooled and solidified to obtain an injection-molded PPR pipe;
[0020] S3.2: Place the injection molded PPR pipe in a high-pressure and high-temperature annealing furnace, heat the furnace to 80-85℃ at a heating rate of 5-10℃ / min, and increase the pressure to 100-200MPa at a pressure increase rate of 10-20MPa / min, and keep the temperature and pressure for 20-25 minutes. Under the condition of constant pressure, heat it to 100-105℃ at a heating rate of 5-10℃ / min, keep it warm for 20-25 minutes, continue to keep the pressure constant, heat it to 120-125℃ at a heating rate of 5-10℃ / min, keep it warm for 40-45 minutes, then stop heating, adjust the pressure in the furnace to 50-55MPa, cool the injection molded PPR pipe to 50-55℃ with the furnace, then take it out, and cool it naturally to room temperature to obtain a PPR pipe with low-temperature resistance and toughness.
[0021] Furthermore, in step S1.1, the particle size of the boron powder is 50-100 μm, the boron content is more than 95%, and the apparent density is 20-50 g / cm.
[0022] Furthermore, in step S1.1, the ball milling solvent is a mixture of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:(1-2).
[0023] Furthermore, the initiator in step S2.1 is potassium persulfate.
[0024] Furthermore, in step S2.2, the mass ratio of pimelic acid to anhydrous ethanol in the pimelic acid ethanol solution is 1:(20-22).
[0025] Furthermore, the pelletizing speed of the pelletizer in step S3.1 is the same as the extrusion speed of the twin-screw extruder.
[0026] A PPR pipe with low-temperature resistance and toughness is prepared by the above-mentioned preparation process of the PPR pipe with low-temperature resistance and toughness.
[0027] The beneficial effects are: 1. The present invention can significantly shorten the annealing and heat preservation time by placing the prepared injection-molded PPR pipe in a high-pressure and high-temperature annealing furnace for pressurized annealing, thereby improving production efficiency. At the same time, annealing under pressure helps to evenly distribute the temperature inside the material, improve the overall mechanical properties, effectively promote the arrangement and orientation of polymer molecular chains, improve the crystallinity of the material, and have a significant effect on improving strength and toughness. Annealing in a pressurized environment can improve the low-temperature and room-temperature toughness of the PPR pipe by changing the movement behavior of the polymer chain, reduce the risk of brittle fracture, and can also release internal stress more quickly and prevent its regeneration, thereby improving the stability of the PPR pipe.
[0028] 2. The present invention prepares ball-milled boron powder by mixing boron powder, anhydrous ethanol and N,N-dimethylformamide, ultrasonically dispersing the ball-milled boron powder in a sulfuric acid solution for acid treatment, and then ultrasonically dispersing the ball-milled boron powder in a polyvinyl pyrrolidone solution for atomization drying to prepare boronene microspheres. In this process, anhydrous ethanol and N,N-dimethylformamide penetrate into the interlayer of the boron powder by ball milling with the boron powder, and then further expand the interlayer spacing by ultrasonic dispersion in sulfuric acid, and then disperse in a polyvinyl pyrrolidone solution for atomization drying, which can not only further expand the interlayer spacing, but also enable two-dimensional boronene to form three-dimensional boronene microspheres together. Due to the high strength and high flexibility of boronene, when the boronene microspheres are blended with random copolymer polypropylene, the impact strength can be improved, thereby improving the low-temperature toughness of the PPR material. In addition, the high thermal conductivity of boronene can enable the material to further maintain a uniform distribution of the internal temperature during the pressurized annealing and heat preservation process, thereby improving the crystallinity of the material and improving the toughness of the PPR material at low temperatures.
[0029] 3. The present invention prepares polystyrene-borene microspheres by adding borene microspheres during the polymerization reaction of acrylic acid and styrene, and then disperses the microspheres in anhydrous ethanol and adds calcium nitrate and stirs to fully complex the calcium ions with polyvinyl pyrrolidone and aggregate on the surface of the polystyrene-borene microspheres. Then, an ethanol solution of pimelic acid is added to react with the calcium ions on the surface of the polystyrene-borene microspheres to generate calcium pimelate, thereby obtaining calcium pimelate / polystyrene-borene microspheres with calcium pimelate as a shell and polystyrene-borene microspheres as a core. After the microspheres are blended and extruded with random copolymer polypropylene to form a pipe, more nucleation sites are provided by optimizing the interface interaction between the microspheres and the polypropylene, reducing the entanglement of the polypropylene molecular chains and promoting more uniform crystallization behavior, thereby facilitating the nucleation and stabilization of the β phase of the polypropylene, thereby further improving the low-temperature toughness of the PPR pipe. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a flow chart of the process for preparing a PPR pipe with low-temperature resistance and toughness used in an embodiment of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] A preparation process of a PPR pipe with low temperature toughness resistance, such as Figure 1 As shown, the following steps are included:
[0034] S1: Preparation of Borophene Microspheres
[0035] S1.1: 2 parts by weight of boron powder, 4 parts by weight of ball milling solvent and 30 parts by weight of tungsten steel grinding balls with a particle size of 1 mm are placed in a ball mill, wherein the particle size of the boron powder is 50 μm, the boron content is 95%, and the apparent density is 20 g / cm; the ball milling solvent is a mixture of anhydrous ethanol and N, N-dimethylformamide in a volume ratio of 1:1; then the ball mill is placed in a high-energy ball mill, the speed is adjusted to 400 rpm, and ball milling is performed for 6 hours to obtain ball-milled boron powder; the ball-milled boron powder and a sulfuric acid solution with a mass percentage concentration of 20% are mixed in a solid-liquid ratio of 1:8 and placed in a container; ultrasonic dispersion is performed at a power of 400 W for 25 minutes, and then the mixture is allowed to stand for 1 hour. After filtering, the mixture is rinsed with deionized water 3 times, and then placed in an oven and dried at 65°C to obtain pretreated boron powder;
[0036] S1.2: Mix polyvinyl pyrrolidone and deionized water in a mass ratio of 1:4 and stir until the polyvinyl pyrrolidone is completely dissolved to obtain a polyvinyl pyrrolidone solution, mix 2 parts by weight of pretreated boron powder and 4 parts by weight of the polyvinyl pyrrolidone solution and place them in an ultrasonic disperser, perform ultrasonic dispersion at a power of 400 W for 15 minutes, then place them in a spray dryer, and perform atomization drying at a temperature of 120°C under a nitrogen atmosphere to obtain boron microspheres.
[0037] S2: Composite of polystyrene, boron nitride microspheres and calcium pimelate
[0038] S2.1: 1 part by weight of potassium persulfate and 0.3 part by weight of polyvinyl pyrrolidone are placed in a container, 80 parts by weight of deionized water are added, and nitrogen is introduced into the resulting mixed solution while stirring at a stirring speed of 500 rpm for 30 minutes, then 1 part by weight of acrylic acid and 4 parts by weight of styrene are added, and the mixture is stirred at a stirring speed of 300 rpm for 15 minutes, and then placed in a nitrogen atmosphere, heated to 45° C. for 3 hours of pre-reaction, and then 1.5 parts by weight of boron nitride microspheres are added, and the mixture is stirred at a stirring speed of 300 rpm for 20 minutes, and then the temperature is continued to be raised to 80° C. for 10 hours of reaction, and polystyrene-boron nitride microspheres are obtained after drying;
[0039] S2.2: Mix 4 parts by weight of polystyrene-borophene microspheres and 60 parts by weight of anhydrous ethanol and place them in an ultrasonic disperser, perform ultrasonic dispersion at a power of 500 W for 20 minutes, then add 0.2 parts by weight of calcium nitrate, stir at 60°C at a stirring speed of 200 rpm for 30 minutes, let stand for 30 minutes, add 12 parts by weight of ethanol solution of pimelic acid and stir evenly, the mass ratio of pimelic acid to anhydrous ethanol in the ethanol solution of pimelic acid is 1:20, maintain the temperature of 60°C for 2 hours to obtain a reaction dispersion, filter the reaction dispersion to obtain a solid substance, and then place it in an oven for drying at 70°C to obtain calcium pimelic acid / polystyrene-borophene microspheres.
[0040] S3: Compound injection molding and graded pressure annealing of PPR pipes
[0041] S3.1: Calcium pimelate / polystyrene-borophene microspheres and random copolymer polypropylene are added into a mixer at a mass ratio of 1:5 and mixed evenly to obtain a premix, the premix is placed in a twin-screw extruder, and melt-blended and extruded at a processing temperature of 200°C, a current intensity of 13 mA, and a rotation speed of 100 rpm, and pelletized by a pelletizer at the same pelletizing speed as the extrusion speed of the twin-screw extruder to obtain a blended masterbatch, the blended masterbatch is injected into a closed mold by an injection molding machine, and then cooled and solidified to obtain an injection-molded PPR pipe;
[0042] S3.2: Place the injection molded PPR pipe in a high-pressure and high-temperature annealing furnace, raise the temperature to 80°C at a heating rate of 5°C / min, and raise the pressure to 100MPa at a pressure rising rate of 10MPa / min, and keep the temperature and pressure for 20 minutes. Under the condition of constant pressure, raise the temperature to 100°C at a heating rate of 5°C / min, keep it warm for 20 minutes, continue to keep the pressure constant, raise the temperature to 120°C at a heating rate of 5°C / min, keep it warm for 40 minutes, then stop heating, adjust the pressure in the furnace to 50MPa, cool the injection molded PPR pipe to 50°C with the furnace, then take it out, and naturally cool it to room temperature to obtain a PPR pipe with low-temperature resistance and toughness.
[0043] Example 2
[0044] A preparation process of a PPR pipe with low temperature toughness resistance, such as Figure 1 As shown, the following steps are included:
[0045] S1: Preparation of Borophene Microspheres
[0046] S1.1: 3 parts by weight of boron powder, 6 parts by weight of ball milling solvent and 35 parts by weight of tungsten steel grinding balls with a particle size of 1 mm are placed in a ball mill, wherein the particle size of the boron powder is 50 μm, the boron content is 95%, and the apparent density is 20 g / cm; the ball milling solvent is a mixture of anhydrous ethanol and N, N-dimethylformamide in a volume ratio of 1:2; then the ball mill is placed in a high-energy ball mill, the speed is adjusted to 400 rpm, and ball milling is performed for 6 hours to obtain ball-milled boron powder; the ball-milled boron powder and a sulfuric acid solution with a mass percentage concentration of 20% are mixed in a solid-liquid ratio of 1:10 and placed in a container; ultrasonic dispersion is performed at a power of 400 W for 25 minutes, and then the mixture is allowed to stand for 1 hour. After filtering, the mixture is rinsed with deionized water 3 times, and then placed in an oven and dried at 65°C to obtain pretreated boron powder;
[0047] S1.2: Mix polyvinyl pyrrolidone and deionized water in a mass ratio of 1:5 and stir until the polyvinyl pyrrolidone is completely dissolved to obtain a polyvinyl pyrrolidone solution. Mix 3 parts by weight of pretreated boron powder and 6 parts by weight of the polyvinyl pyrrolidone solution and place them in an ultrasonic disperser. Perform ultrasonic dispersion at a power of 400 W for 15 minutes. Then place them in a spray dryer and perform atomization drying at a temperature of 120°C under a nitrogen atmosphere to obtain boron olefin microspheres.
[0048] S2: Composite of polystyrene, boron nitride microspheres and calcium pimelate
[0049] S2.1: 2 parts by weight of potassium persulfate and 0.4 parts by weight of polyvinyl pyrrolidone are placed in a container, 100 parts by weight of deionized water are added, nitrogen is introduced into the obtained mixed solution while stirring at a stirring speed of 500 rpm for 30 minutes, 1.5 parts by weight of acrylic acid and 4.5 parts by weight of styrene are then added, the mixture is stirred at a stirring speed of 300 rpm for 15 minutes, and then placed in a nitrogen atmosphere, heated to 45°C for 3 hours of pre-reaction, 2 parts by weight of boron nitride microspheres are added, the mixture is stirred at a stirring speed of 300 rpm for 20 minutes, and then the temperature is continued to be raised to 80°C for 10 hours of reaction, and polystyrene-boron nitride microspheres are obtained after drying;
[0050] S2.2: Mix 6 parts by weight of polystyrene-borophene microspheres and 80 parts by weight of anhydrous ethanol and place them in an ultrasonic disperser, perform ultrasonic dispersion at a power of 500 W for 20 minutes, then add 0.3 parts by weight of calcium nitrate, stir at 60°C at a stirring speed of 200 rpm for 30 minutes, let stand for 30 minutes, add 16 parts by weight of ethanol solution of pimelic acid and stir evenly, the mass ratio of pimelic acid to anhydrous ethanol in the ethanol solution of pimelic acid is 1:22, maintain the temperature of 60°C for 2 hours to obtain a reaction dispersion, filter the reaction dispersion to obtain a solid substance, and then place it in an oven for drying at 70°C to obtain calcium pimelic acid / polystyrene-borophene microspheres.
[0051] S3: Compound injection molding and graded pressure annealing of PPR pipes
[0052] S3.1: Calcium pimelate / polystyrene-borophene microspheres and random copolymer polypropylene are added to a mixer at a mass ratio of 1:6 and mixed evenly to obtain a premix, the premix is placed in a twin-screw extruder, and melt-blended and extruded at a processing temperature of 200°C, a current intensity of 13 mA, and a rotation speed of 100 rpm, and pelletized by a pelletizer at the same pelletizing speed as the extrusion speed of the twin-screw extruder to obtain a blended masterbatch, and the blended masterbatch is injected into a closed mold by an injection molding machine, and then cooled and solidified to obtain an injection-molded PPR pipe;
[0053] S3.2: Place the injection molded PPR pipe in a high-pressure and high-temperature annealing furnace, raise the temperature to 80°C at a heating rate of 5°C / min, and raise the pressure to 100MPa at a pressure rising rate of 10MPa / min, and keep the temperature and pressure for 20 minutes. Under the condition of constant pressure, raise the temperature to 100°C at a heating rate of 5°C / min, keep it warm for 20 minutes, continue to keep the pressure constant, raise the temperature to 120°C at a heating rate of 5°C / min, keep it warm for 40 minutes, then stop heating, adjust the pressure in the furnace to 50MPa, cool the injection molded PPR pipe to 50°C with the furnace, then take it out, and naturally cool it to room temperature to obtain a PPR pipe with low-temperature resistance and toughness.
[0054] Example 3
[0055] A preparation process of a PPR pipe with low temperature toughness resistance, such as Figure 1 As shown, the following steps are included:
[0056] S1: Preparation of Borophene Microspheres
[0057] S1.1: 2 parts by weight of boron powder, 4 parts by weight of ball milling solvent and 30 parts by weight of tungsten steel grinding balls with a particle size of 2 mm are placed in a ball mill, wherein the particle size of the boron powder is 100 μm, the boron content is 99%, and the apparent density is 50 g / cm; the ball milling solvent is a mixture of anhydrous ethanol and N, N-dimethylformamide in a volume ratio of 1:1; then the ball mill is placed in a high-energy ball mill, the speed is adjusted to 600 rpm, and ball milling is performed for 8 hours to obtain ball-milled boron powder; the ball-milled boron powder and a sulfuric acid solution with a mass percentage concentration of 25% are mixed in a solid-liquid ratio of 1:8 and placed in a container; ultrasonic dispersion is performed at a power of 450 W for 30 minutes, and then the mixture is allowed to stand for 1.5 hours, filtered, rinsed with deionized water 4 times, and then placed in an oven and dried at 70°C to obtain pretreated boron powder;
[0058] S1.2: Mix polyvinyl pyrrolidone and deionized water in a mass ratio of 1:4 and stir until the polyvinyl pyrrolidone is completely dissolved to obtain a polyvinyl pyrrolidone solution. Mix 2 parts by weight of pretreated boron powder and 4 parts by weight of the polyvinyl pyrrolidone solution and place them in an ultrasonic disperser. Perform ultrasonic dispersion at a power of 450 W for 20 minutes. Then place them in a spray dryer and perform atomization drying at a temperature of 150°C under a nitrogen atmosphere to obtain boron microspheres.
[0059] S2: Composite of polystyrene, boron nitride microspheres and calcium pimelate
[0060] S2.1: 1 part by weight of potassium persulfate and 0.3 part by weight of polyvinyl pyrrolidone are placed in a container, 80 parts by weight of deionized water are added, and nitrogen is introduced into the resulting mixed solution while stirring at a stirring speed of 600 rpm for 40 minutes, then 1 part by weight of acrylic acid and 4 parts by weight of styrene are added, and the mixture is stirred at a stirring speed of 350 rpm for 20 minutes, and then placed in a nitrogen atmosphere, heated to 50° C. for 4 hours of pre-reaction, and then 2 parts by weight of boron nitride microspheres are added, and the mixture is stirred at a stirring speed of 350 rpm for 25 minutes, and then the temperature is continued to be raised to 85° C. for 12 hours of reaction, and polystyrene-boron nitride microspheres are obtained after drying;
[0061] S2.2: Mix 4 parts by weight of polystyrene-borophene microspheres and 60 parts by weight of anhydrous ethanol and place them in an ultrasonic disperser, perform ultrasonic dispersion at a power of 550 W for 25 minutes, then add 0.2 parts by weight of calcium nitrate, stir at a stirring speed of 250 rpm at 65°C for 35 minutes, let stand for 35 minutes, add 12 parts by weight of ethanol solution of pimelic acid and stir evenly, the mass ratio of pimelic acid to anhydrous ethanol in the ethanol solution of pimelic acid is 1:20, maintain the temperature of 65°C for 3 hours to obtain a reaction dispersion, filter the reaction dispersion to obtain a solid substance, and then place it in an oven for drying at 75°C to obtain calcium pimelic acid / polystyrene-borophene microspheres.
[0062] S3: Compound injection molding and graded pressure annealing of PPR pipes
[0063] S3.1: Calcium pimelate / polystyrene-borophene microspheres and random copolymer polypropylene are added into a mixer at a mass ratio of 1:5 and mixed evenly to obtain a premix, and the premix is placed in a twin-screw extruder, and melt-blended and extruded at a processing temperature of 225°C, a current intensity of 15 mA, and a rotation speed of 150 rpm, and pelletized by a pelletizer at the same pelletizing speed as the extrusion speed of the twin-screw extruder to obtain a blended masterbatch, and the blended masterbatch is injected into a closed mold by an injection molding machine, and then cooled and solidified to obtain an injection-molded PPR pipe;
[0064] S3.2: Place the injection molded PPR pipe in a high-pressure and high-temperature annealing furnace, raise the temperature to 85°C at a heating rate of 10°C / min, and raise the pressure to 200MPa at a pressure rising rate of 20MPa / min, and keep the temperature and pressure for 25 minutes. Under the condition of constant pressure, raise the temperature to 105°C at a heating rate of 10°C / min, keep it warm for 25 minutes, continue to keep the pressure constant, raise the temperature to 125°C at a heating rate of 10°C / min, keep it warm for 45 minutes, then stop heating, adjust the pressure in the furnace to 55MPa, cool the injection molded PPR pipe to 55°C with the furnace, then take it out, and naturally cool it to room temperature to obtain a PPR pipe with low-temperature resistance and toughness.
[0065] Comparative Example 1: Compared with Example 1, the difference of Comparative Example 1 is that Comparative Example 1 removes step S3.2, and sends the injection molded PPR pipe to an ordinary annealing and roasting furnace for annealing. The annealing temperature is controlled at 120°C and maintained for 80 minutes. The heating rate is 5°C / min. After the annealing is completed, it is cooled to 50°C in the furnace and taken out, and naturally cooled to room temperature. The remaining steps are the same as in Example 1, and a PPR pipe with low-temperature resistance and toughness is obtained. The obtained PPR pipe with low-temperature resistance and toughness is recorded as Comparative Example 1.
[0066] Comparative Example 2: Compared with Example 1, the difference of Comparative Example 2 is that Comparative Example 2 removes step S1, does not add borophene microspheres in step S2.1, and obtains polystyrene microspheres, replaces the polystyrene-borophene microspheres in step S2.2 with polystyrene microspheres to obtain calcium pimelate / polystyrene microspheres, and replaces the calcium pimelate / polystyrene-borophene microspheres in step S3.1 with calcium pimelate / polystyrene microspheres to obtain injection-molded PPR pipes. The remaining steps are the same as in Example 1, and the obtained PPR pipe with low-temperature resistance and toughness is recorded as Comparative Example 2.
[0067] Comparative Example 3: Compared with Example 1, the difference of Comparative Example 3 is that step S2 is removed in Comparative Example 3. In step S3.1, calcium pimelate, boron nitrile microspheres, polystyrene and random copolymer polypropylene are added to a mixer in a mass ratio of 0.4:1.5:4:30 and mixed evenly to obtain a premix. The remaining steps are the same as in Example 1. The obtained PPR pipe with low-temperature resistance and toughness is recorded as Comparative Example 3.
[0068] The PPR pipes with low temperature toughness resistance prepared in Examples 1-3 and Comparative Examples 1-3 with the same diameter were cut into samples of the same length for testing. The testing method is as follows, and the test record data is tabulated as shown in Table 1:
[0069] Low temperature drop hammer impact: Use a drop hammer impact tester to perform a drop hammer impact test on the samples, with a hammer weight of 1kg and a drop height of 1m. Take 100 samples each and store them at -18℃ for 24h. Each sample completes the drop hammer impact test within 15s, and the sample breakage ratio (breakage number / 100) is recorded;
[0070] Crystallinity test: XRD test was performed on five block samples cut from the sample tube, using a Cu-Ka target, with an X-ray wavelength of 0.154 nm, a scanning voltage and a scanning current of 40 kV and 40 mA, respectively, a scanning range of θ = 5 to 30°, a scanning speed of 5° / min, and the average value of the crystallinity X% was recorded.
[0071] Hydrostatic test: Take 10 samples each and conduct hydrostatic test according to GB / T6111-2003. The specific test conditions are 20℃, 16MPa for 1.5h. Observe whether the PPR pipe is cracked or leaking, and record the average time of cracking and leakage.
[0072] Table 1: Properties of PPR pipes with low temperature toughness
[0073]
[0074] According to the test data of the embodiment in Table 1 and the test data of Comparative Example 1, it can be seen that the graded pressurized annealing treatment can effectively promote the arrangement and orientation of polymer molecular chains, improve the crystallinity of PPR pipes, and reduce the low-temperature drop hammer breakage rate of PPR pipes from 21% to 3%. Annealing in a pressurized environment can not only improve the low-temperature toughness of PPR pipes and reduce the risk of brittle fracture, but also release internal stress more quickly and prevent its regeneration, thereby improving the stability of the material.
[0075] According to the test data of the embodiment in Table 1 and the test data of Comparative Example 2, it can be seen that without adding borophene microspheres to the PPR pipe, the low-temperature drop hammer breakage rate of the PPR pipe decreases to a certain extent, which can prove the high strength and high flexibility of borophene. When borophene microspheres are blended with random copolymer polypropylene, the impact strength can be improved, thereby improving the low-temperature toughness of the PPR pipe, and the crystallinity is also reduced. It can be proved that the high thermal conductivity of borophene can also enable the material to further maintain the uniform distribution of the internal temperature during the pressurized annealing and insulation process, thereby improving the crystallinity of the material.
[0076] According to the test data of the embodiment in Table 1 and the test data of Comparative Example 3, it can be seen that the crystallinity and low-temperature toughness of the prepared PPR pipe are reduced when calcium pimelate / polystyrene-borene microspheres are not prepared for blending with the PPR material. This proves that the preparation of calcium pimelate / polystyrene-borene microspheres can promote more uniform crystallization behavior, thereby further improving the low-temperature toughness of the PPR pipe.
[0077] In summary, the PPR pipe provided by the present invention has excellent comprehensive mechanical properties, especially the low-temperature impact resistance is greatly improved, thereby ensuring the safety and reliability of PPR use.
[0078] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A process for preparing a PPR pipe with low temperature toughness, characterized in that: The following steps are involved: S1: Preparation of Borophene Microspheres Boron powder, a ball milling solvent and a tungsten steel grinding ball are mixed and ball milled to obtain ball milled boron powder, the ball milled boron powder is ultrasonically dispersed in a sulfuric acid solution, and after standing, the powder is filtered, washed and dried in sequence to obtain pretreated boron powder, polyvinyl pyrrolidone is dissolved in deionized water to obtain a polyvinyl pyrrolidone solution, and the pretreated boron powder is ultrasonically dispersed in the polyvinyl pyrrolidone solution, and boronene microspheres are obtained after atomization and drying; S2: Composite of polystyrene, boron nitride microspheres and calcium pimelate Potassium persulfate, polyvinyl pyrrolidone and deionized water are mixed and stirred while nitrogen is introduced, acrylic acid and styrene are added and stirred, the temperature is increased in a nitrogen atmosphere for pre-reaction, boron nitrate microspheres are added, the temperature is continued to be increased after stirring for reaction, and polystyrene-borene microspheres are obtained by drying, the polystyrene-borene microspheres are ultrasonically dispersed in anhydrous ethanol, calcium nitrate is added, the temperature is increased and stirred, after standing, a pimelic acid ethanol solution is added and stirred evenly, the reaction is kept warm, and then filtered and dried to obtain calcium pimelic acid / polystyrene-borene microspheres; S3: Compound injection molding and graded pressure annealing of PPR pipes Calcium pimelate / polystyrene-borophene microspheres and random copolymer polypropylene are mixed and placed in a twin-screw extruder for co-extrusion and pelletization to obtain a blended masterbatch. The blended masterbatch is injection-molded by an injection molding machine and then cooled and solidified to obtain an injection-molded PPR pipe. The injection-molded PPR pipe is placed in a high-pressure and high-temperature annealing furnace for three-stage pressurized and heated annealing treatment to obtain a PPR pipe with low-temperature resistance and toughness.
2. The process for preparing a PPR pipe with low temperature toughness resistance according to claim 1, characterized in that: Step S1 prepares borophene microspheres, comprising the following steps: S1.1: 2-3 parts by weight of boron powder, 4-6 parts by weight of ball milling solvent and 30-35 parts by weight of tungsten steel grinding balls with a particle size of 1-2 mm are placed in a ball mill, and then placed in a high-energy ball mill, the rotation speed is adjusted to 400-600rpm, and ball milling is performed for 6-8 hours to obtain ball-milled boron powder, and the ball-milled boron powder and a sulfuric acid solution with a mass percentage concentration of 20-25% are mixed in a solid-liquid ratio of 1: (8-10) and placed in a container, and ultrasonic dispersion is performed at a power of 400-450W for 25-30 minutes using an ultrasonic disperser, and then allowed to stand for 1-1.5 hours, filtered, rinsed with deionized water for 3-4 times, and then placed in an oven and dried at 65-70°C to obtain pretreated boron powder; S1.2: Mix polyvinyl pyrrolidone and deionized water in a mass ratio of 1:(4-5) and stir until the polyvinyl pyrrolidone is completely dissolved to obtain a polyvinyl pyrrolidone solution, mix 2-3 parts by weight of pretreated boron powder and 4-6 parts by weight of polyvinyl pyrrolidone solution and place them in an ultrasonic disperser, perform ultrasonic dispersion at a power of 400-450 W for 15-20 minutes, then place them in a spray dryer, and perform atomization drying at a temperature of 120-150°C under a nitrogen atmosphere to obtain boron olefin microspheres.
3. The process for preparing a PPR pipe with low temperature toughness resistance according to claim 2, characterized in that: Step S2: Compounding of polystyrene, borophene microspheres and calcium pimelate, comprising the following steps: S2.1: 1-2 parts by weight of an initiator and 0.3-0.4 parts by weight of polyvinyl pyrrolidone are placed in a container, 80-100 parts by weight of deionized water are added, and nitrogen is introduced into the resulting mixed solution while stirring at a stirring speed of 500-600 rpm for 30-40 minutes, then 1-1.5 parts by weight of acrylic acid and 4-4.5 parts by weight of styrene are added, and the mixture is stirred at a stirring speed of 300-350 rpm for 15-20 minutes, and then placed in a nitrogen atmosphere, heated to 45-50° C. for 3-4 hours of pre-reaction, and then 1.5-2 parts by weight of boron nitride microspheres are added, and the mixture is stirred at a stirring speed of 300-350 rpm for 20-25 minutes, and then the temperature is continued to be raised to 80-85° C. for 10-12 hours of reaction, and polystyrene-boron nitride microspheres are obtained after drying; S2.2: 4-6 parts by weight of polystyrene-borophene microspheres and 60-80 parts by weight of anhydrous ethanol are mixed and placed in an ultrasonic disperser, and ultrasonic dispersion is performed at a power of 500-550 W for 20-25 minutes, and then 0.2-0.3 parts by weight of calcium nitrate are added, and the mixture is stirred at a stirring speed of 200-250 rpm at 60-65° C. for 30-35 minutes, and then allowed to stand for 30-35 minutes, and 12-16 parts by weight of ethanol solution of pimelic acid are added and stirred evenly, and the temperature is maintained at 60-65° C. for reaction for 2-3 hours to obtain a reaction dispersion liquid, and the reaction dispersion liquid is filtered to obtain a solid substance, which is then placed in an oven for drying at 70-75° C. to obtain calcium pimelic acid / polystyrene-borophene microspheres.
4. The process for preparing a PPR pipe with low temperature toughness resistance according to claim 3 is characterized in that: Step S3: the blending injection molding and graded pressure annealing of the PPR pipe comprises the following steps: S3.1: Calcium pimelate / polystyrene-borophene microspheres and random copolymer polypropylene are added into a mixer at a mass ratio of 1:(5-6) and mixed evenly to obtain a premix, the premix is placed in a twin-screw extruder, and melt-blended and extruded at a processing temperature of 200-225°C, a current intensity of 13-15mA, and a rotation speed of 100-150rpm, and pelletized by a pelletizer to obtain a blended masterbatch, and the blended masterbatch is injected into a closed mold by an injection molding machine, and then cooled and solidified to obtain an injection-molded PPR pipe; S3.2: Place the injection molded PPR pipe in a high-pressure and high-temperature annealing furnace, heat the furnace to 80-85℃ at a heating rate of 5-10℃ / min, and increase the pressure to 100-200MPa at a pressure increase rate of 10-20MPa / min, and keep the temperature and pressure for 20-25 minutes. Under the condition of constant pressure, heat it to 100-105℃ at a heating rate of 5-10℃ / min, keep it warm for 20-25 minutes, continue to keep the pressure constant, heat it to 120-125℃ at a heating rate of 5-10℃ / min, keep it warm for 40-45 minutes, then stop heating, adjust the pressure in the furnace to 50-55MPa, cool the injection molded PPR pipe to 50-55℃ with the furnace, then take it out, and cool it naturally to room temperature to obtain a PPR pipe with low-temperature resistance and toughness.
5. The process for preparing a PPR pipe with low temperature toughness resistance according to claim 2, characterized in that: In step S1.1, the particle size of the boron powder is 50-100 μm, the boron content is more than 95%, and the apparent density is 20-50 g / cm.
6. The process for preparing a PPR pipe with low temperature toughness resistance according to claim 2, characterized in that: In step S1.1, the ball milling solvent is a mixture of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:(1-2).
7. The process for preparing a PPR pipe with low temperature toughness resistance according to claim 3 is characterized in that: The initiator in step S2.1 is potassium persulfate.
8. The process for preparing a PPR pipe with low temperature toughness resistance according to claim 3, characterized in that: The mass ratio of pimelic acid to anhydrous ethanol in the pimelic acid ethanol solution in step S2.2 is 1:(20-22).
9. The process for preparing a PPR pipe with low temperature toughness resistance according to claim 4, characterized in that: The pelletizing speed of the pelletizer in step S3.1 is the same as the extrusion speed of the twin-screw extruder.
10. A PPR pipe with low temperature toughness, characterized in that: The pipe is prepared by the preparation process of a PPR pipe having low temperature resistance and toughness according to any one of claims 1 to 9.